Analisis Isi Media NU Online dalam Mencegah Radikalisme di Indonesia - Salsabila, Desi Fitri; Choiriyah; Muslimin (Indonesian Journal Publisher, 2024)
The background to this research is the discourse about radicalism in Indonesia which has become a hot topic of conversation in 2021 after the bombing in front of the Makassar Cathedral Church, one of which is Media NU Online. The research method used is qualitative with a quantitative approach, data was obtained through literature review of discourse texts and documentation. The theory used in this research is Teun Andreas Van Dijk's Critical Discourse Analysis theory. The results of this research are that NU Online tries to fight Indonesian radicalism by confirming the Aswaja teachings contained in a news report delivered by the Deputy General Chairperson of the PBNU (Period 2010-2015) H. As'ad Said Ali that the nadhliyin are to revive the Aswaja tradition in everyday life -day and implementing the attitude of Religious Moderation contained in four news stories and one article, through the institutions under its auspices, through NU Online media inviting nahdliyin in particular to live in harmony between religious communities, be tolerant and implement an attitude of religious moderation.